The Assyrian genocide cultural and political legacies - Travis, Hannibal (Milton Park, Abingdon, Oxon Routledge, 2017)
List of judicial decisions cited -- Table of legislation -- Introduction : the assyrian genocide across history : collective memory, legal theory, and power politics / Hannibal Travis -- The term Seyfo in historical perspective / Michael Abdalla -- The atrocities against the Assyrians in 1915 : a legal perspective / Sara Demir -- The Ottoman genocide of the Assyrians in Persia / Anahit Khosroeva -- Abduction, rape and genocide : Urmia's Assyrian girls and women / Eden Naby -- Genocide/Seyfo and how resistance became a way of life / Sait Cetinoglu (Abdulmesih BarAbraham, trans.) -- Lady Surma : pillar of the Assyrian nation, 1883-1975 / Stavros Stavridis --The Assyrian delegation in the Paris Peace Conference / Racho Donef -- The Assyrian "Concept of unity" after Seyfo / Aryo Makko -- Exile or extinction : the Assyrian genocide from 1915 to 2015 / Hannibal Travis -- Epilogue : tombstones and inverted crosses / Nineb Lamassu.
Keywords: Genocide -- History -- 20th century -- Turkey; Genocide -- History -- 20th century -- Iraq; Assyrians -- History -- 20th century -- Turkey; Assyrians -- History -- 20th century -- Iraq; Minorities -- History -- 20th century -- Turkey; Minorities -- History -- 20th century -- Iraq; Christians -- History -- 20th century -- Turkey; Christians -- History -- 20th century -- Iraq; Genocide ; Turkey ; History ; 20th century; Genocide ; Iraq ; History ; 20th century; Assyrians ; Turkey ; History ; 20th century; Assyrians ; Iraq ; History ; 20th century; Minorities ; Turkey ; History ; 20th century; Minorities ; Iraq ; History ; 20th century; Christians ; Turkey ; History ; 20th century; Christians ; Iraq ; History ; 20th century; Iraq ; Ethnic relations; Turkey ; Ethnic relations; Electronic books; Iraq -- Ethnic relations; Turkey -- Ethnic relations; Electronic books